2022
DOI: 10.3390/w14040556
|View full text |Cite
|
Sign up to set email alerts
|

Surface Water Change Detection via Water Indices and Predictive Modeling Using Remote Sensing Imagery: A Case Study of Nuntasi-Tuzla Lake, Romania

Abstract: Water body feature extraction using a remote sensing technique represents an important tool in the investigation of water resources and hydrological drought assessment. Nuntasi-Tuzla Lake, a component of the Danube Delta Natural Reserve, is located on the Romanian Black Sea littoral. On account of an event in summer 2020, when the lake surface water decreased significantly, this study aims to identify the variation of the Nuntasi-Tuzla Lake surface water over a long-term period in correlation with human interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Serban et al [15] implemented a model to detect the change in surface water. This case study is taken from a lake named Nuntasi-Tuzla from Romania.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Serban et al [15] implemented a model to detect the change in surface water. This case study is taken from a lake named Nuntasi-Tuzla from Romania.…”
Section: Literature Surveymentioning
confidence: 99%
“…Nadam is the best optimization technique, which is an improved version of Adam. Gradient descent is the basic optimization technique further versions like Adam, Nadam were introduced to remove flaws in the Gradient Descent [15]. NAG momentum is used in the Nadam optimizer.…”
Section: Module 4: Nadam Optimizermentioning
confidence: 99%
“…5 indices NDVI, NDWI, MNDWI, WNDWI and WRI were used to check the changes. The results showed that Landsat images were evaluated to have a higher kappa coefficient and overall accuracy than MADIS images due to their high spatial resolution [1]. Also, in 2022, using remote sensing and GIS methods, the coastal wetlands in Burolus Lake in Egypt were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…15 Spectral water indices are more accurate compared to other methods such as classification techniques, or linear unmixing. 7,16,17 Among the spectral indices of water most used in the literature, in 18 the authors developed the Normalized Difference Water Index (NDWI) using green and near-infrared (NIR) spectral ranges to maximize water characteristics. 18 replaced NIR with shortwave infrared (SWIR) and derived the modified NDWI (MNDWI).…”
Section: Introductionmentioning
confidence: 99%